Sensory Perception in Cetaceans: Part I—Current Knowledge about Dolphin Senses As a Representative Species - Kremers, Dorothee; Célérier, Aurélie; Schaal, Benoist; Campagna, Sylvie; Trabalon, Marie; Böye, Martin; Hausberger, Martine; Lemasson, Alban (Frontiers in Ecology and Evolution, 2016)
A large part of the literature on sensory perception and behavior in dolphins is devoted to its well-developed vocal and echolocation abilities. In this review, we aim to augment current knowledge by examining the literature on dolphins’ entire “Merkwelt” (which refers to everything a subject perceives, creating a crucial part of the subject’s Umwelt). We will show that despite extensive knowledge on audition, aspects such as context relatedness, the social function of vocalizations or socio-sexual recognition, remain poorly understood. Therefore, we propose areas for further lines of investigation. Recent studies have shown that the sensory world of dolphins might well be much more diverse than initially thought. Indeed, although underwater and aerial visual systems differ in dolphins, they have both been shown to be important. Much debated electro- and magnetoreception appear to be functional senses according to recent studies. Finally, another neglected area is chemoreception. We will summarize neuroanatomical and physiological data on olfaction and taste, as well as corresponding behavioral evidence. Taken together, we will identify a number of technical and conceptual reasons for why chemosensory data appear contradictory, which is much debated in the literature. In summary, this article aims to provide both an overview of the current knowledge on dolphin perception, but also offer a basis for further discussion and potential new lines of research.